An Analysis of the Sigificance and Religious Purpose of Upah-Upah Tondi Tradition Contained in Batak Mandailing Tribe - Siregar, Elvi Fauziah; Aissyah Octaweni; Rahmawati (PT Inovasi Pratama Internasional, 2025)
The objective of this descriptive qualitative research is to analyze the significance and religious purpose of the Upah-Upah Tondi tradition contained in the Batak Mandailing tribe. The data for this research are from the literature. The data sources of this research are journals, books, and articles about the Upah-Upah Tondi tradition. There are significant differences in the Upah-Upah Tondi tradition. They can be divided into the materials used and behavioral processes. The materials used in the Upah-Upah Tondi tradition are customized according to the level of illness. Ordinary illnesses typically involve the use of boiled eggs. Symbolically, a round egg, consisting of a yolk and white, represents the wholeness of the spirit and body. Severe illnesses usually affect chicken and goat heads. Chicken is the most important requirement in this tradition because it symbolizes hope in the recovery process from the illness. Therefore, the behavioral process in Upah-Upah Tondi, like the rotation of the tray to the right, symbolizes goodness. Batak Mandailing people believe that good things come from the right, whereas the rotation of the tray to the right symbolizes goodness. The religious purpose of the Upah-Upah tradition includes the value of faith, gratitude, and connecting relatives